Clinical outcomes in youth beyond the first year of type 1 diabetes: Results of the Pediatric Diabetes Consortium (PDC) type 1 diabetes new onset (NeOn) study. Issue 7 (19th October 2016) - Cengiz, Eda; Cheng, Peiyao; Ruedy, Katrina J.; Kollman, Craig; Tamborlane, William V.; Klingensmith, Georgeanna J.; Gal, Robin L.; Silverstein, Janet; Lee, Joyce; Redondo, Maria J.; Beck, Roy W.
Abstract : Objective: Current data are limited on the course of type 1 diabetes (T1D) in children and adolescents through the first few years of diabetes. The Pediatric Diabetes Consortium T1D new onset (NeOn) Study was undertaken to prospectively assess natural history and clinical outcomes in children treated at 7 US diabetes centers from the time of diagnosis. This paper describes clinical outcomes in the T1D NeOn cohort during the first 3 years postdiagnosis. Results: A total of 1048 participants (mean age 9.2 years, 49% female, 65% non‐Hispanic White) were enrolled between July 2009 and April 2011. Mean glycated hemoglobin (HbA1c) (±SD) was 7.2% (55 mmol/mol) at 3 months, followed by a progressive rise to 8.4% (68 mmol/mol) at 36 months postdiagnosis, with only 30% of participants achieving target HbA1c<7.5% (58 mmol/mol). The percentage of participants in partial remission estimated by insulin dose adjusted HbA1c [HbA1c % + (4×insulin dose unit/kg/24 h)] ≤9 sharply declined from 23% at 12 months to 7% at 36 months. The percentage of participants developing diabetic ketoacidosis (DKA) was 1% in the first year after diagnosis, increasing to 6% in years 2 and 3. Conclusions: These results demonstrate the gradual decline in glycemic control due to waning residual endogenous insulin secretion with increasing duration of T1D in children and adolescents. These data indicate the need to translate recent advances in automated insulin delivery, new insulin analogs, and adjunctive pharmacologic agents into novel treatment strategies to maintain optimal glycemic control even early in the course of T1D.